O princípio da gestão democrática e a participação nos conselhos de escola - Fujiye, Tieko (2014)
The theme of participation in the School Council is established as a challenge to the effective achievement of democratic management in education which is necessary and inevitable moment of democratization of Brazilian society . Therefore , in this paper , it is established preliminarily , a relationship between the process of democratization / civil society participation and the phenomenon that occurs through the School Council , one of the most representative forums of democratic management in the school setting as the legal documents show . The category set to seize the perceptions of teachers and parents about the principle and practice of democratic management was " participation " in the School Council , under the understanding that the perceptions of this category , extracted from the agents involved in the activities and purposes of one unit public school elementary schools of the East Zone of São Paulo , could identify the strengths and difficulties of building a democratic culture within the school. The object of this study was chosen with a view to enable the realization of more informed interventions in the dynamics of the Board as a collective body of exercising democratic management , thereby seeking to meet a line of action of the Master Program in Management and Educational Practices.